Impact of light intensity and tank color on growth and development of largemouth bass, Micropterus nigricans, during early life history - Anneleen Swanepoel; Nelson S. Parajuli; Kaylan Martin; Kyle R. Wood; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; Timothy J. Bruce; D. Allen Davis; Ian A.E. Butts (Aquaculture, 2026)

Is There Mush-room for Bettongs on Dirk Hartog Island? Environmental DNA Assessment of Food Resource Availability for Fauna Translocations - Rebecca J. Quah; Saul J. Cowen; Kelly J. Rayner; Aaron J. Brace; Robert A. Davis; Harriet R. Mills; Anna J. M. Hopkins (Ecosystems, 2026)
Conservation translocations require careful assessment of dietary resources to ensure population viability. Here, we used environmental DNA metabarcoding to characterise fungal assemblages across three major habitat types on Dirk Hartog Island, Western Australia, prior to the planned reintroduction of two threatened mycophagous species: the boodie ( Bettongia lesueur ) and woylie ( Bettongia ogilbyi ). We detected 243 fungal ASVs, of which 75 represented taxa that are likely to produce macroscopic fruiting bodies accessible to mycophagous mammals. Ectomycorrhizal fungi dominated all habitats, with Pezizaceae being the most abundant family—a pattern consistent with known dietary preferences of both species across multiple Australian locations. Fungal community composition differed significantly among habitat types, with birrida (saltpan), dwarf scrub, and shrub-steppe each supporting distinct assemblages. Comparative analysis with recent dietary studies revealed approximately 50% overlap between the island’s fungal communities and boodie and woylie diets, indicating suitable resource availability. While potential dietary overlap (25–33%) exists between species, the island’s size and spatial distribution of fungal resources suggest competition is unlikely to limit initial population establishment. These findings demonstrate that Dirk Hartog Island possesses a diversity of fungal resources suitable to support both species, with birrida habitat recommended as preferential release sites following rainfall events to maximise foraging success.

The impact of serial translocation bottlenecks on the genetic diversity of Anegada Rock Iguanas (Cyclura pinguis) in the British Virgin Islands - Giuliano Colosimo; Zachary Dykema; Mark E. Welch; Gad Perry; Zachary Harlow; Heidi Davis; Kelly A. Bradley; Gabriele Gentile; Glenn P. Gerber (Conservation Genetics, 2026)

The Meanings and Dividends of Man the Hunter - Vivek V. Venkataraman; Edward H. Hagen; Duncan Stibbard-Hawkes; Raymond Hames; Sheina Lew-Levy; Haneul Jang; Luke Glowacki; Jordie Hoffman; Karen Kramer; Helen Elizabeth Davis; Kathrine Starkweather; Barry Hewlett; et al. (Evolution and Human Behavior, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Predator and prey density effects on early life-history performance of largemouth bass (Micropterus nigricans) in an indoor recirculating aquaculture system - Nelson S. Parajuli; Josh Sakmar; Allen Nicholls; Anita M. Kelly; Luke A. Roy; D. Allen Davis; Timothy J. Bruce; Matthew K. Litvak; Ian A.E. Butts (Aquaculture, 2026)

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Group concept mapping to develop a salon-based HPV self-collection intervention - Kelly N. B. Palmer; Namoonga M. Mantina; Adebola Adegboyega; Itunu O. Sokale; Kathleen Pryor; Azaria Suero-Davis; Trevon Brooks; Jennifer Hatcher (Cancer Causes & Control, 2025)
Background Black women in the US face higher cervical cancer mortality rates due to delayed diagnoses linked to lower screening rates. Contributing factors include provider bias, costs, and limited access, particularly affecting women aged 40–64. While innovative approaches like clinical and home-based HPV self-collection exist, equitable dissemination remains challenging. Distributing HPV self-collection kits in unconventional sites like hair salons may offer a solution. Using concept mapping, we gathered community insights to design a salon-based cervical cancer screening intervention. Methods We employed groupwisdom™ and REDCap platforms for community-based participatory intervention development. Participants included members of the Black Community Advisory Council of Tucson (Black CACTus), comprising hairstylists ( n = 3), salon clients ( n = 4), and healthcare providers( n = 3), all identifying as Black women aged 23–53. Concept mapping included: 1) Brainstorming statements, 2) Sorting statements into thematic clusters, 3) Rating importance and feasibility, 4) Reviewing the cluster map, and 5) Evaluating a draft intervention. Results Brainstorming produced 39 statements, forming six clusters: 1) Program Promotion, 2) Insurance, Cost & Benefits, 3) Communication Considerations, 4) Information and Education, 5) Overall Logistics and Process, and 6) Sample Collection. Communication Considerations and Sample Collection were rated most important, with Communication Considerations also ranking highest for feasibility. Communication Considerations, Information and Education, and Sample Collection were the highest rated when importance and feasibility were considered together. Conclusions Engaging community perspectives is essential for adapting cancer screening from clinical settings to community spaces like hair salons. This collaborative concept mapping approach identified strategies to enhance cervical cancer screening access and uptake among Black women.

Investigation of dietary exogenous protease and humic substance on growth, disease resistance to Flavobacterium covae and immune responses in juvenile channel catfish ( Ictalurus punctatus ) - Abdulmalik A. Oladipupo; Anita M. Kelly; D. Allen Davis; Timothy J. Bruce (Journal of Fish Diseases, 2025)
Many bacterial pathogens impact the US catfish industry, and disease control can be challenging for producers. Columnaris disease in channel catfish, Ictalurus punctatus , is primarily caused by Flavobacterium covae (formerly F. columnare ). Immunostimulants may enhance nonspecific immune responses and offer an alternative to antibiotic treatments in catfish. Furthermore, dietary protein sources and inclusions are also essential to fish health and nutrition and may enhance overall fish performance in pond culture. The current project evaluated two immunostimulants: a protease complex (PC) and a humic substance (HS) derived from a reed‐sedge peat product. A 60‐day trial examined the effects of five diets on growth performance, immune response and resistance to experimental F. covae infection in channel catfish. Diets included a high‐quality fishmeal diet (32%; CF32), a high‐protein soy‐based diet (32%; C32), a low‐protein soy‐based diet (28%; C28; predominately used in industry), a low‐protein soy diet supplemented with C28 + PC at 175 g metric ton −1 and C28 + HS in a low‐protein diet at 23 g metric ton −1 . Following feeding for 60 d, juvenile channel catfish were sampled for growth performance and baseline health indicators ( n = 3; body mucus, blood for sera, kidney and spleen). A subset of fish was then subjected to an immersion‐based in vivo challenge trial with F. covae (ALG‐00‐530; 10 6 CFU mL −1 exposure). At 60d post‐initiation, there were no dietary differences in the relative growth rate ( p = .063) or thermal growth coefficient ( p = .055), but the 32% diets generally appeared to perform best. Post‐challenge, the C32 group's mortality was higher than the C28 + PC ( p = .006) and C28 + HS diets ( p = .005). Although not significant, the C28 and CF32 groups also demonstrated higher mortality compared to both PC and HS diets. Sera lysozyme concentration was found to increase following pathogen challenge ( p p il‐1β , il‐8 , tnf‐α and tgf‐β ) were observed at trial midpoint and post‐infection when compared to 60d. The C28 treatment was found to have lower tnf‐α expression than the C28 + PC ( p = .042) and C28 + HS ( p = .042) groups following exposure to F. covae . These challenge data suggest that the immunostimulants (PC and HS) in plant‐based protein may be beneficial in protecting against F. covae when offered in low‐protein channel catfish diets.

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Dynamic manganese cycling in the northern Gulf of Mexico - Jessalyn E. Davis; Rebecca S. Robinson; Emily R. Estes; Veronique E. Oldham; Evan A. Solomon; Roger P. Kelly; Katherine E. Bell; Joseph A. Resing; Randelle M. Bundy (Marine Chemistry, 2024)

Evaluation of molecular-based methods for the detection and quantification of Cryptosporidium spp. in wastewater - Oumaima Hachimi; Rebecca Falender; Gabriel Davis; Rispa Vranka Wafula; Melissa Sutton; June Bancroft; Paul Cieslak; Christine Kelly; Devrim Kaya; Tyler Radniecki (Science of The Total Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Biodistribution and toxic potential of silver nanoparticles when introduced to the female rat reproductive tract - Nathan A. Koonce; Ammu Mathew; Ioana-Mihaela Popescu; Kelly Davis; Doug Wagner; Gokulan Kuppan; Mugimane Manjanatha; Julian E.A. Leakey; Anil K. Patri (NanoImpact, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

A Nourishing Space: Growing Client-Centered Health Professionals - Francilia Brito Silva; Samantha Honse; Miteshri Prajapati; Kathleen Davis; Marilyn Massey Stokes; Michelle Kelly; Kara Belt (Journal of Nutrition Education and Behavior, 2024)

Repeat treatment of organotypic airway cultures with ethyl methanesulfonate causes accumulation of somatic cell mutations without expansion of bronchial-carcinoma-specific cancer driver mutations - Yiying Wang; Yuan Le; Kelly L. Harris; Ying Chen; Xilin Li; Jennifer Faske; Rebecca A. Wynne; Roberta A. Mittelstaedt; Xuefei Cao; Jaime Miranda-Colon; Lana Elkins; Levan Muskhelishvili; et al. (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Female foragers sometimes hunt, yet gendered divisions of labor are real: a comment on Anderson et al. (2023) The Myth of Man the Hunter - Vivek V. Venkataraman; Jordie Hoffman; Kyle Farquharson; Helen Elizabeth Davis; Edward H. Hagen; Raymond B. Hames; Barry S. Hewlett; Luke Glowacki; Haneul Jang; Robert Kelly; Karen Kramer; Sheina Lew-Levy; et al. (Evolution and Human Behavior, 2024)

Spring applied phosphorus loss with cover crops in no-till terraced field - Harpreet Kaur; Kelly A. Nelson; Gurbir Singh; Gurpreet Kaur; Morgan P. Davis (Journal of Environmental Management, 2024)

Parallel evaluation of alternative skin barrier models and excised human skin for dermal absorption studies in vitro - Alec T. Salminen; Kelly J. Davis; Robert P. Felton; Nathania Nischal; Linda S. VonTungeln; Frederick A. Beland; Kristy Derr; Paul C. Brown; Marc Ferrer; Linda M. Katz; Nicole C. Kleinstreuer; Jonathan Leshin; et al. (Toxicology in Vitro, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Role of Sociodemographic, Academic, and Individual Health Behaviors on Psychological Well-Being Among College Students - Leandra Durham; Lizzy Davis; Tara Kelly; Rebecca Kennedy; Daniel Smith; Yenni Cedillo (Journal of Nutrition Education and Behavior, 2023)

Evaluation of aqueous magnesium concentration on performance of Pacific white shrimp (Litopenaeus vannamei) cultured in low salinity water of West Alabama, USA - David P. Hernández; Hisham A. Abdelrahman; Harsha S.C. Galkanda-Arachchige; Anita M. Kelly; Ian A.E. Butts; D. Allen Davis; Benjamin H. Beck; Luke A. Roy (Aquaculture, 2023)

Anti-inflammatory actions of β-funaltrexamine in a mouse model of lipopolysaccharide-induced inflammation - Stephanie Myers; Kelly McCracken; Daniel J. Buck; J. Thomas Curtis; Randall L. Davis (Inflammopharmacology, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Delimiting the cryptic diversity and host preferences of Sycophila parasitoid wasps associated with oak galls using phylogenomic data - Yuanmeng M. Zhang; Sofia I. Sheikh; Anna K. G. Ward; Andrew A. Forbes; Kirsten M. Prior; Graham N. Stone; Michael W. Gates; Scott P. Egan; Linyi Zhang; Charles Davis; Kelly L. Weinersmith; George Melika; et al. (Molecular Ecology, 2022)
Cryptic species diversity is a major challenge regarding the species‐rich community of parasitoids attacking oak gall wasps due to a high degree of sexual dimorphism, morphological plasticity, small size and poorly known biology. As such, we know very little about the number of species present, nor the evolutionary forces responsible for generating this diversity. One hypothesis is that trait diversity in the gall wasps, including the morphology of the galls they induce, has evolved in response to selection imposed by the parasitoid community, with reciprocal selection driving diversification of the parasitoids. Using a rare, continental‐scale data set of Sycophila parasitoid wasps reared from 44 species of cynipid galls from 18 species of oak across the USA, we combined mitochondrial DNA barcodes, ultraconserved elements (UCEs), morphological and natural history data to delimit putative species. Using these results, we generate the first large‐scale assessment of ecological specialization and host association in this species‐rich group, with implications for evolutionary ecology and biocontrol. We find most Sycophila target specific subsets of available cynipid host galls with similar morphologies, and generally attack larger galls. Our results suggest that parasitoid wasps such as Sycophila have adaptations allowing them to exploit particular host trait combinations, while hosts with contrasting traits are resistant to attack. These findings support the tritrophic niche concept for the structuring of plant–herbivore–parasitoid communities.

Chronic exposure to lead acetate promotes changes in the alveolar bone of rats: microstructural and physical–chemical characterization - Lodinikki Lemoy Davis; Walessa Alana Bragança Aragão; Géssica de Oliveira Lopes; Luciana Guimaraes Eiró; Alexandre Rodrigues Freire; Felippe Bevilacqua Prado; Ana Cláudia Rossi; Allan da Silva Cruz; Kelly das Graças Fernandes Dantas; Alan Rodrigo Leal Albuquerque; Simone Patricia Aranha Paz; Rômulo Simões Angélica; et al. (Environmental Science and Pollution Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

SNAPSHOT USA 2019: a coordinated national camera trap survey of the United States - Michael V. Cove; Roland Kays; Helen Bontrager; Claire Bresnan; Monica Lasky; Taylor Frerichs; Renee Klann; Thomas E. Lee; Seth C. Crockett; Anthony P. Crupi; Katherine C. B. Weiss; Helen Rowe; et al. (Ecology, 2021)
With the accelerating pace of global change, it is imperative that we obtain rapid inventories of the status and distribution of wildlife for ecological inferences and conservation planning. To address this challenge, we launched the SNAPSHOT USA project, a collaborative survey of terrestrial wildlife populations using camera traps across the United States. For our first annual survey, we compiled data across all 50 states during a 14‐week period (17 August–24 November of 2019). We sampled wildlife at 1,509 camera trap sites from 110 camera trap arrays covering 12 different ecoregions across four development zones. This effort resulted in 166,036 unique detections of 83 species of mammals and 17 species of birds. All images were processed through the Smithsonian’s eMammal camera trap data repository and included an expert review phase to ensure taxonomic accuracy of data, resulting in each picture being reviewed at least twice. The results represent a timely and standardized camera trap survey of the United States. All of the 2019 survey data are made available herein. We are currently repeating surveys in fall 2020, opening up the opportunity to other institutions and cooperators to expand coverage of all the urban–wild gradients and ecophysiographic regions of the country. Future data will be available as the database is updated at eMammal.si.edu/snapshot‐usa, as will future data paper submissions. These data will be useful for local and macroecological research including the examination of community assembly, effects of environmental and anthropogenic landscape variables, effects of fragmentation and extinction debt dynamics, as well as species‐specific population dynamics and conservation action plans. There are no copyright restrictions; please cite this paper when using the data for publication.

Integration of transcriptome analysis with pathophysiological endpoints to evaluate cigarette smoke toxicity in an in vitro human airway tissue model - Rui Xiong; Yue Wu; Qiangen Wu; Levan Muskhelishvili; Kelly Davis; Priya Tripathi; Ying Chen; Tao Chen; Matthew Bryant; Hans Rosenfeldt; Sheila M. Healy; Xuefei Cao (Archives of Toxicology, 2021)
Exposure to cigarette smoke (CS) is a known risk factor in the pathogenesis of smoking-caused diseases, such as chronic obstructive pulmonary diseases (COPD) and lung cancer. To assess the effects of CS on the function and phenotype of airway epithelial cells, we developed a novel repeated treatment protocol and comprehensively evaluated the progression of key molecular, functional, and structural abnormalities induced by CS in a human in vitro air–liquid-interface (ALI) airway tissue model. Cultures were exposed to CS (diluted with 0.5 L/min, 1.0 L/min, and 4.0 L/min clean air) generated from smoking five 3R4F University of Kentucky reference cigarettes under the International Organization for Standardization (ISO) machine smoking regimen, every other day for 4 weeks (3 days per week, 40 min/day). By integrating the transcriptomics-based approach with the in vitro pathophysiological measurements, we demonstrated CS-mediated effects on oxidative stress, pro-inflammatory cytokines and matrix metalloproteinases (MMPs), ciliary function, expression and secretion of mucins, and squamous cell differentiation that are highly consistent with abnormalities observed in airways of smokers. Enrichment analysis on the transcriptomic profiles of the ALI cultures revealed key molecular pathways, such as xenobiotic metabolism, oxidative stress, and inflammatory responses that were perturbed in response to CS exposure. These responses, in turn, may trigger aberrant tissue remodeling, eventually leading to the onset of respiratory diseases. Furthermore, changes of a panel of genes known to be disturbed in smokers with COPD were successfully reproduced in the ALI cultures exposed to CS. In summary, findings from this study suggest that such an integrative approach may be a useful tool for identifying genes and adverse cellular events caused by inhaled toxicants, like CS.

Correction to: Persistence of Tuber melanosporum in truffle orchards in North Carolina, USA - Inga Meadows; Kelly Gaskill; Leonora Stefanile; Suzette Sharpe; Jeanine Davis (Mycorrhiza, 2020)

Persistence of Tuber melanosporum in truffle orchards in North Carolina, USA - Inga Meadows; Kelly Gaskill; Leonora Stefanile; Suzette Sharpe; Jeanine Davis (Mycorrhiza, 2020)

Effects of Saltwater Pulses on Soil Microbial Enzymes and Organic Matter Breakdown in Freshwater and Brackish Coastal Wetlands - Shelby Servais; John S. Kominoski; Carlos Coronado-Molina; Laura Bauman; Stephen E. Davis; Evelyn E. Gaiser; Stephen Kelly; Christopher Madden; Viviana Mazzei; David Rudnik; Fabiola Santamaria; Fred H. Sklar; et al. (Estuaries and Coasts, 2020)

Experimental Saltwater Intrusion Drives Rapid Soil Elevation and Carbon Loss in Freshwater and Brackish Everglades Marshes - Sean P. Charles; John S. Kominoski; Tiffany G. Troxler; Evelyn E. Gaiser; Shelby Servais; Benjamin J. Wilson; Stephen E. Davis; Fred H. Sklar; Carlos Coronado-Molina; Christopher J. Madden; Steve Kelly; David T. Rudnick (Estuaries and Coasts, 2019)

Embracing an interdisciplinary approach to plastics pollution awareness and action - Sara L. Belontz; Patricia L. Corcoran; Heather Davis; Kathleen A. Hill; Kelly Jazvac; Kirsty Robertson; Kelly Wood (Ambio, 2019)

Functional and Compositional Responses of Periphyton Mats to Simulated Saltwater Intrusion in the Southern Everglades - Viviana Mazzei; Evelyn E. Gaiser; John S. Kominoski; Benjamin J. Wilson; Shelby Servais; Laura Bauman; Stephen E. Davis; Steve Kelly; Fred H. Sklar; David T. Rudnick; Jemma Stachelek; Tiffany G. Troxler (Estuaries and Coasts, 2018)

Ecological correlates of the spatial co‐occurrence of sympatric mammalian carnivores worldwide - Courtney L. Davis; Lindsey N. Rich; Zach J. Farris; Marcella J. Kelly; Mario S. Di Bitetti; Yamil Di Blanco; Sebastian Albanesi; Mohammad S. Farhadinia; Navid Gholikhani; Sandra Hamel; Bart J. Harmsen; Claudia Wultsch; et al. (Ecology Letters, 2018)
The composition of local mammalian carnivore communities has far‐reaching effects on terrestrial ecosystems worldwide. To better understand how carnivore communities are structured, we analysed camera trap data for 108 087 trap days across 12 countries spanning five continents. We estimate local probabilities of co‐occurrence among 768 species pairs from the order Carnivora and evaluate how shared ecological traits correlate with probabilities of co‐occurrence. Within individual study areas, species pairs co‐occurred more frequently than expected at random. Co‐occurrence probabilities were greatest for species pairs that shared ecological traits including similar body size, temporal activity pattern and diet. However, co‐occurrence decreased as compared to other species pairs when the pair included a large‐bodied carnivore. Our results suggest that a combination of shared traits and top‐down regulation by large carnivores shape local carnivore communities globally.

Contrasting impacts of highly invasive plant species on flower-visiting insect communities - Emily S. Davis; Ruth Kelly; Christine A. Maggs; Jane C. Stout (Biodiversity and Conservation, 2018)

First detection of Edwardsiella ictaluri (Proteobacteria: Enterobacteriaceae) in wild Australian catfish - E Kelly; P A J Martin; S Gibson‐Kueh; D L Morgan; B C Ebner; J Donaldson; N Buller; D A Crook; S Brooks; A M Davis; M P Hammer; L Foyle; et al. (Journal of Fish Diseases, 2018)
The bacterium Edwardsiella ictaluri is considered to be one of the most significant pathogens of farmed catfish in the United States of America and has also caused mortalities in farmed and wild fishes in many other parts of the world. E. ictaluri is not believed to be present in wild fish populations in Australia, although it has previously been detected in imported ornamental fishes held in quarantine facilities. In an attempt to confirm freedom from the bacterium in Australian native fishes, we undertook a risk‐based survey of wild catfishes from 15 sites across northern Australia. E. ictaluri was detected by selective culturing, followed by DNA testing, in Wet Tropics tandan ( Tandanus tropicanus ) from the Tully River, at a prevalence of 0.40 (95% CI 0.21–0.61). The bacterium was not found in fishes sampled from any of the other 14 sites. This is the first report of E. ictaluri in wild fishes in Australia.

Breeding biology of Arctic terns (Sterna paradisaea) in the Canadian High Arctic - Mark L. Mallory; Kelly A. Boadway; S. E. Davis; M. Maftei; Antony W. Diamond (Polar Biology, 2017)

Assessing global patterns in mammalian carnivore occupancy and richness by integrating local camera trap surveys - Lindsey N. Rich; Courtney L. Davis; Zach J. Farris; David A. W. Miller; Jody M. Tucker; Sandra Hamel; Mohammad S. Farhadinia; Robin Steenweg; Mario S. Di Bitetti; Kanchan Thapa; Mamadou D. Kane; S. Sunarto; et al. (Global Ecology and Biogeography, 2017)
Aim Biodiversity loss is a major driver of ecosystem change, yet the ecological data required to detect and mitigate losses are often lacking. Recently, camera trap surveys have been suggested as a method for sampling local wildlife communities, because these observations can be collated into a global monitoring network. To demonstrate the potential of camera traps for global monitoring, we assembled data from multiple local camera trap surveys to evaluate the interchange between fine‐ and broad‐scale processes impacting mammalian carnivore communities. Location Argentina, Belize, Botswana, Canada, Indonesia, Iran, Madagascar, Nepal, Norway, Senegal, South Africa, and the U.S.A. Methods We gathered camera trap data, totalling > 100,000 trap nights, from across five continents. To analyse local and species‐specific responses to anthropogenic and environmental variables, we fitted multispecies occurrence models to each study area. To analyse global‐level responses, we then fitted a multispecies, multi‐area occurrence model. Results We recorded 4,805 detections of 96 mammalian carnivore species photographed across 1,714 camera stations located in 12 countries. At the global level, our models revealed that carnivore richness and occupancy within study areas was positively associated with prey availability. Occupancy within study areas also tended to increase with greater protection and greater distances to roads. The strength of these relationships, however, differed among countries. Main conclusions We developed a research framework for leveraging global camera trap data to evaluate patterns of mammalian carnivore occurrence and richness across multiple spatial scales. Our research highlights the importance of intact prey populations and protected areas in conserving carnivore communities. Our research also highlights the potential of camera traps for monitoring wildlife communities and provides a case study for how this can be achieved on a global scale. We encourage greater integration and standardization among camera trap studies worldwide, which would help inform effective conservation planning for wildlife populations both locally and globally.

Blueprints of Effective Biodiversity and Conservation Knowledge Products That Support Marine Policy - Lauren V. Weatherdon; Ward Appeltans; Nadine Bowles-Newark; Thomas M. Brooks; Frances E. Davis; Katherine Despot-Belmonte; Stephen Fletcher; Cristina Garilao; Craig Hilton-Taylor; Tim Hirsch; Diego Juffe-Bignoli; Kristin Kaschner; et al. (Frontiers in Marine Science, 2017)

Patient and genetic counselor perceptions of in-person versus telephone genetic counseling for hereditary breast/ovarian cancer - Aryana S. Jacobs; Marc D. Schwartz; Heiddis Valdimarsdottir; Rachel H. Nusbaum; Gillian W. Hooker; Tiffani A. DeMarco; Jessica E. Heinzmann; Wendy McKinnon; Shelley R. McCormick; Claire Davis; Andrea D. Forman; Alexandra Perez Lebensohn; et al. (Familial Cancer, 2016)

Characterisation of the clinical and activated T cell response to repeat delayed-type hypersensitivity skin challenges in human subjects, with KLH and PPD, as a potential model to test T cell-targeted therapies - Alexandra Belson; Tim Schmidt; Disala Fernando; Kelly Hardes; Nicola Scott; Sara Brett; Deborah Clark; João Joaquim Oliveira; Bill Davis; Simon McHugh; John Stone (Inflammation Research, 2016)

Composition, Alteration, and Texture of Fault-Related Rocks from Safod Core and Surface Outcrop Analogs: Evidence for Deformation Processes and Fluid-Rock Interactions - Kelly K. Bradbury; Colter R. Davis; John W. Shervais; Susanne U. Janecke; James P. Evans (Pure and Applied Geophysics, 2015)

A Longman's beaked whale ( Indopacetus pacificus ) strands in Maui, Hawaii, with first case of morbillivirus in the central Pacific - Kristi L. West; Susan Sanchez; David Rotstein; Kelly M. Robertson; Sophie Dennison; Gregg Levine; Nicole Davis; David Schofield; Charles W. Potter; Brenda Jensen (Marine Mammal Science, 2013)

Breeding biology of Sabine’s gull (Xema sabini) in the Canadian high Arctic - Mark L. Mallory; Kelly A. Boadway; Shanti E. Davis; Mark Maftei (Polar Biology, 2012)

The Business of Forest Enterprise / Urban Ecosystems - Steve Narolski; Richard Bin Mei; Rafael De La Torre; Mike Clutter; John Pait; Maggi Kelly; Frederick Cubbage; Patricio MacDonagh; Gustavo Balmelli; Virginia Morales Olmos; Adriana Bussoni; Rafael Rubilar; et al. (Journal of Forestry, 2011)
22In 2009, five unique methods were used to inspect vegetation-related conditions along Bonneville Power Administration (BPA) rights-of-way (ROW). Some methods were trials that BPA committed to execute as part of a settlement with its regional regulatory organization, the Western Electric Coordination Council (WECC), for violations of reliability standards from vegetation grow-in related outages. A combination of simple, stratified, and 100% sampling were used to compare and contrast each inspection technique. A cost-replacement comparison between all inspection techniques was performed, weighting efficacy of one technique to another in the form of replacement value. Cost-benefit and return-on-investment analyses were also computed. From these analyses, LiDAR proved most effective in identifying vegetation related clearance issues but proved most costly, at least for initial establishment. The average cost of LiDAR trended downward with subsequent flights. The most cost effective method was using helicopters with either Natural Resource Specialists (NRS) or Transmission Line Maintenance (TLM) personnel serving as aerial observers, but this methodology proved the most inaccurate. Furthermore, the ancillary utility of LiDAR for related asset assessments more than justify the initial expense, includes power line sag ratings, asset (structures, insulators, roads, etc.) health, and encroachment identification. It is hypothesized that incorporating LiDAR sampling from 20% of the whole system per year to 40+ % may actually represent a cost-savings when allocating available resources system-wide. This data can also be used for documenting compliance with all federal regulations and requirements, as well as substitute for manual on-the-ground inspections, whether by BPA staff or third-party contractors.

Physician Awareness and Referral to National Smoking Cessation Quitlines and Web-Based Resources - Lila J. Finney Rutten; Kia Davis; Linda Squiers; Erik Augustson; Kelly Blake (Journal of Cancer Education, 2011)

Isolation of a Ve homolog, mVe1, and its relationship to verticillium wilt resistance in Mentha longifolia (L.) Huds - Kelly Vining; Thomas Davis (Molecular Genetics and Genomics, 2009)

Functional imaging of microdomains in cell membranes - James Duggan; Ghadir Jamal; Mark Tilley; Ben Davis; Graeme McKenzie; Kelly Vere; Michael G. Somekh; Paul O’Shea; Helen Harris (European Biophysics Journal, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Herbivore-induced infochemicals influence foraging behaviour in two intertidal predators - Ross A. Coleman; Sorain J. Ramchunder; Kelly M. Davis; A. John Moody; Andrew Foggo (Oecologia, 2007)

Average age-specific cumulative risk of breast cancer according to type and site of germline mutations in BRCA1 and BRCA2 estimated from multiple-case breast cancer families attending Australian family cancer clinics - Clare L. Scott; Mark A. Jenkins; Melissa C. Southey; Tracey A. Davis; Jennifer A. Leary; Douglas F. Easton; Kelly-Anne Phillips; John L. Hopper (Human Genetics, 2003)

The hunting strategy of white sharks ( Carcharodon carcharias ) near a seal colony - A. Peter Klimley; Burney J. Le Boeuf; Kelly M. Cantara; John E. Richert; Scott F. Davis; Sean Van Sommeran; John T. Kelly (Marine Biology, 2001)

Radio-acoustic positioning as a tool for studying site-specific behavior of the white shark and other large marine species - A. Peter Klimley; Burney J. Le Boeuf; Kelly M. Cantara; John E. Richert; Scott F. Davis; S. Van Sommeran (Marine Biology, 2001)